Unlocking care: continuing mental health care for prisoners and their families - David Baker
Summary People in prison have a higher incidence of mental illness than the general population. The prevalence of mental health issues is higher again for women prisoners. Although evidence suggests that some improvement can be achieved during imprisonment, new research reported in this paper finds that average mental health deteriorates in the year following release. The imprisonment of a close family member also places strains on families, including increased mental distress. The effects on children can be long lasting. While the mental health needs of prisoners have been recognised by federal, state and territory governments, the needs of their families has received less attention. Providing continued care from prison into the community is known as ‘throughcare’. The continuation of health services helps overcome some of the barriers people face re-connecting with services in the community and may contribute to a reversal of the decline in mental health following release. Accessing mental health services will often be one challenge among many, including the reestablishment of relationships with children and partners, finding secure housing, maintaining substance-use programs or counselling and finding a job. Coordinating social services for people returning to society will improve the overall success of transition. Families can also play an important role in supporting this transition – therefore, investing more resources into understanding their needs will have a flow-on benefit for former prisoners and society more generally. The design and delivery of mental health services for adults and children needs greater research and coordinated policy development. Federal leadership has led to the measuring and reporting of prisoner mental health. This program should be extended to include measurements following release and widened to include the families of prisoners. Interest in throughcare a decade ago resulted in a move towards the integration of prison and community health services. A majority of jurisdictions – Victoria, Queensland and Western Australia being the exceptions – now have an integrated health service, providing the foundation for the development of throughcare services. Improved delivery of mental health services potentially reduces the risk of re-imprisonment; providing wider personal, familial and community benefits